2018
DOI: 10.3390/sym10040112
|View full text |Cite
|
Sign up to set email alerts
|

New Similarity Solutions of a Generalized Variable-Coefficient Gardner Equation with Forcing Term

Abstract: The compatibility method is used for a generalized variable-coefficient Gardner equation (GVGE) with a forcing term. By the compatibility of the considered equation and a non-classical symmetry of a given form, four types of symmetry are obtained. Then, by solving the characteristic equations of symmetry, the GVGE is reduced to variable coefficients ordinary differential equations, and rich varieties of new similarity solutions are presented. Our results show that the compatibility method can be employed for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Next, to solve Equation ( 10), we substitute Equation (11) into Equation (10). Note that the order of magnitude of   0  A v v is 10 0 and that of  …”
Section: Asymptotic Analytical Solution Of the Angular Motion Of A Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Next, to solve Equation ( 10), we substitute Equation (11) into Equation (10). Note that the order of magnitude of   0  A v v is 10 0 and that of  …”
Section: Asymptotic Analytical Solution Of the Angular Motion Of A Pr...mentioning
confidence: 99%
“…The equation of angular motion for a projectile is a second-order non-homogeneous ordinary differential equation with variable coefficients. For this kind of equation, research has shown that it is possible to obtain an accurate analytical solution only when the equation is in a specific form [10][11][12]. However, the angular motion equation is not in a specific form.…”
mentioning
confidence: 99%
“…The Lie-group method, originally proposed by Sophus Lie, is a classical method to determine the symmetry reduction of partial differential equations (PDEs) [13][14][15][16]. During the past several decades, there have been many extensions of the Lie-group method such as the nonclassical Lie group method [17], the CK direct method [18], the direct symmetry method [19], and so on [20][21][22][23][24]. Among them, the direct symmetry method is an effective approach for seeking symmetry reductions.…”
Section: Introductionmentioning
confidence: 99%